REAL-LIFE EXPERIENCE OF TENOFOVIR ALAFENAMIDE FUMARATE: THE PYTHAGOREAN COHORT - Karasahin, Omer; Kalkan, Irem Akdemir; Dal, Tuba; Toplu, Sibel Altunisik; Harputoglu, Murat; Mete, Ayse Ozlem; Celen, Mustafa (Wiley, 2021)
[Abstract Not Available]